Effect of the addition of different types of oenological commercial tannins on phenolic and sensorial red wine characteristics evolution - Jordão, António (2017)
The main objective of this work was to understand the effect of the addition of different commercial types of oenological tannins on red wine phenolic compounds and sensorial characteristics evolution. So, six different commercial oenological tannins obtained from different sources at an average dosage recommended by the manufactures were added to a red wine. During 120 wine aging days several phenolic parameters were analyzed (including several individual phenolic compounds by HPLC) and also the sensorial characteristics of the wines. Wines treated with oenological tannins showed higher total phenols and ﬂavonoid phenols and lesser color degradation during the aging time considered. After 120 aging days, wines aged with oenological tannins showed After 120 aging days, wines aged with oenological tannins showed more total and individual anthocyanins and signiﬁcantly more red color that induced signiﬁcantly color differences in relation to the untreated wine (especially for the wines treated with condensed tannins). From a sensorial point of view it was also possible to detect a clear differentiation between the wines.